The effect of Euribor on banking profitability: Evidence from the Spanish banking system - David Boto-García; Antonio M. Alvarez; José Ba\~nos-Pino (European Journal of Government and Economics (EJGE), 2021)
This paper studies the relationship between the Euribor rate and the return on average assets (ROAA) of the Spanish banking sector. We use quarterly time series data for the period 1995-2016. Our analysis also controls for bank factors, market concentration, the macroeconomic environment and time effects. The main purpose is to examine how the sector's ROAA varies with the slope of the yield curve. We find evidence of an inverse relationship between the Euribor rate and profitability. We also show that banking profitability is pro-cyclical and is positively related to the stock of performing loans and the national 10-year bond yield.
Keywords: C01; C22; E44; G21; 330; banking profitability; time series; Euribor; interest rate spread; Unconventional Monetary Policy; yield curve